2012
DOI: 10.7251/ssh1201029s
|View full text |Cite
|
Sign up to set email alerts
|

Uticaj programa odbojke na bazične i situaciono-motoričke sposobnosti učenika uzrasta 13 – 14 godina

Abstract: Osnovni cilj ovog istraživanja je bio da se utvrde parcijalne kvantitativne promjene (razlike) bazičnih i situaciono-motoričkih sposobnosti nastale pod uticajem tromjesečnog programa odbojke kod učenika uzrasta 13-14 godina, iz JU OŠ ‚’Tojšići’’, a koji su uključeni u dodatnu nastavu iz područja odbojkaške igre. U istraživanju je primijenjeno 15 varijabli za procjenu bazičnih motoričkih sposobnosti i 5 varijabli za procjenu situaciono-motoričkih sposobnosti. Za analizu eventualnih promjena (razlika) između ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study by Ljubojević et al (2011), basketball content has shown to have positive effects on the development of all the motor skills of boys on a smaller scale and of girls on a larger scale. In numerous studies (Bajrić et al, 2012;Korjenić et al, 2012;Šmigalović et al, 2012;Nešić et al, 2013), the authors applied content from volleyball and obtained results that showed positive effects on the development of basic motor skills and situational motor skills. Sozen (2012) managed to induce positive changes of agility and flexibility in girls by conducting volleyball training as an additional activity in physical education.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ljubojević et al (2011), basketball content has shown to have positive effects on the development of all the motor skills of boys on a smaller scale and of girls on a larger scale. In numerous studies (Bajrić et al, 2012;Korjenić et al, 2012;Šmigalović et al, 2012;Nešić et al, 2013), the authors applied content from volleyball and obtained results that showed positive effects on the development of basic motor skills and situational motor skills. Sozen (2012) managed to induce positive changes of agility and flexibility in girls by conducting volleyball training as an additional activity in physical education.…”
Section: Discussionmentioning
confidence: 99%